Acceptance of Illness, Satisfaction with Life, Sense of Stigmatization, and Quality of Life among People with Psoriasis: A Cross-Sectional Study - Beata Kowalewska; Mateusz Cybulski; Barbara Jankowiak; Elżbieta Krajewska-Kułak (Adis, Springer Healthcare, 2020)
Abstract Introduction Psoriasis is a complex disease with a heterogeneous presentation, which may have a profound effect on the everyday functioning of patients. As a strongly stressogenic disease, psoriasis may cause lack of illness acceptance and contribute to negative changes in self-image. Usually, psoriasis also has a detrimental effect on quality of life. The aim of this study is to determine the levels of illness acceptance, satisfaction with life, stigmatization, and quality of life in people with psoriasis, to analyze relationships among these variables, and to verify whether they are modulated by selected sociodemographic factors. Methods A total of 366 people with psoriasis treated at the Dermatology and Medical Cosmetology Clinic in Białystok were included. The study was conducted using a short survey prepared by the authors and five validated psychometric scales: Acceptance of Illness Scale (AIS), Satisfaction with Life Scale (SWLS), 6-item Stigmatization Scale, 33-item Feelings of Stigmatization Questionnaire, and Dermatology Life Quality Index (DLQI). Results Median AIS score was 24 pts, which corresponds to a moderate level of illness acceptance. The level of illness acceptance among men was significantly higher than among women. More than half of respondents assessed their satisfaction with life as low. Men showed low levels of satisfaction with life slightly more often than women. Patients living in the countryside showed high levels of satisfaction with life significantly more often than those living in cities/towns. Mean scores for the 6-item Stigmatization Scale and the 33-item Feelings of Stigmatization Questionnaire were 8.73 pts and 90.06 pts, respectively, with no significant differences between the results of male and female patients. The DLQI scores for the study group ranged between 0 and 30 pts, with the mean value of 17.81 pts corresponding to a severe deterioration of quality of life. Statistically significant differences between quality of life and all sociodemographic variables were demonstrated. Conclusions People with psoriasis participating in this study showed moderate levels of illness acceptance and stigmatization, low level of satisfaction with life, and moderately deteriorated quality of life. Acceptance of illness was significantly modulated by patient sex. The level of illness acceptance among men was significantly higher than among women. Furthermore, illness acceptance exerted a significant effect on satisfaction with life in psoriasis patients. Place of residence exerted significant effects on satisfaction with life (higher in countryside dwellers), sense of stigmatization (stronger in countryside dwellers), and quality of life (more severely deteriorated in city/town dwellers). Disease duration significantly affected the degree of life satisfaction, sense of stigmatization (measured using a 33-item Feelings of Stigmatization Questionnaire), and quality of life among patients with psoriasis.